Diabetes has no additional impact on retinal ganglion cell loss in a mouse model of spontaneous glaucoma. Issue 3 (May 2023) - Maestroni, Silvia; Belvedere, Arianna; Viganò, Ilaria; Meoni, Cesare; Di Matteo, Federico; Gabellini, Daniela; Bandello, Francesco; Pierro, Luisa; Zerbini, Gianpaolo
Purpose: There is no valid medical treatment for diabetic retinopathy mostly because its pathogenesis remains largely unknown. Early stages of diabetic retinopathy, just like glaucoma, are characterized by the loss of retinal ganglion cells. Whether the two diseases may share a similar pathogenic background is unknown. Methods: To clarify this issue the thickness of retinal nerve fiber layer was studied in vivo by optical coherence tomography in 10 Ins2Akita (diabetic) and 10 C57BL/6J (control) mice. The number of retinal ganglion cells and retina's surface covered by neurofilaments were quantified ex vivo in 12 normoglycemic DBA/2J (glaucoma) and 11 diabetic (alloxan-induced) DBA/2J mice (glaucoma + diabetes). Results: At 16 weeks of age retinal nerve fiber layer was significantly thinner in Ins2Akita mice confirming the neurodegenerative impact of diabetes. Number of retinal ganglion cells and retina's surface covered by neurofilaments were similar in normoglycemic and diabetic DBA/2J mice with the exception of the superior quadrant where the number of retinal ganglion cells was increased in animals with glaucoma + diabetes. Conclusions: In presence of glaucoma, diabetes is unable to induce further retinal ganglion cells loss. The hypothesis that the mechanism leading to retinal ganglion cells loss may be shared by the two diseases cannot be ruled out. Whether early diabetes-driven retinal neurodegeneration could be prevented by neuroprotective treatment proven to be effective in case of glaucoma, remains to be clarified.